Training Planning and Working Memory in Third Graders. Issue 2 (17th May 2013) - Goldin, Andrea Paula; Segretin, María Soledad; Hermida, María Julia; Paz, Luciano; Lipina, Sebastián Javier; Sigman, Mariano
ABSTRACT: Working memory and planning are fundamental cognitive skills supporting fluid reasoning. We show that 2 games that train working memory and planning skills in school‐aged children promote transfer to 2 different tasks: an attentional test and a fluid reasoning test. We also show long‐term improvement of planning and memory capacities in 8‐year‐old children after playing adaptive computer games specifically tailored to entrain these cognitive functions. Working memory capacity expanded from 5 to 7 items by using our games. Furthermore, steady progression in the task indicates that this capacity can be trained rapidly. Planning abilities persisted in a nonmarkovian form of play, where a move is highly influenced by previous moves, avoiding back‐ups. Here, we introduce a public and growing platform (http://www.matemarote.com.ar/) developed for this research which has the potential for wide use in educational research.